Exploiting DNA Endonucleases to Advance Mechanisms of DNA Repair - Marlo K. Thompson; Robert W. Sobol; Aishwarya Prakash (Biology, 2021)
The earliest methods of genome editing, such as zinc-finger nucleases (ZFN) and transcription activator-like effector nucleases (TALENs), utilize customizable DNA-binding motifs to target the genome at specific loci. While these approaches provided sequence-specific gene-editing capacity, the laborious process of designing and synthesizing recombinant nucleases to recognize a specific target sequence, combined with limited target choices and poor editing efficiency, ultimately minimized the broad utility of these systems. The discovery of clustered regularly interspaced short palindromic repeat sequences (CRISPR) in Escherichia coli dates to 1987, yet it was another 20 years before CRISPR and the CRISPR-associated (Cas) proteins were identified as part of the microbial adaptive immune system, by targeting phage DNA, to fight bacteriophage reinfection. By 2013, CRISPR/Cas9 systems had been engineered to allow gene editing in mammalian cells. The ease of design, low cytotoxicity, and increased efficiency have made CRISPR/Cas9 and its related systems the designer nucleases of choice for many. In this review, we discuss the various CRISPR systems and their broad utility in genome manipulation. We will explore how CRISPR-controlled modifications have advanced our understanding of the mechanisms of genome stability, using the modulation of DNA repair genes as examples.